Investigation of the relationship between physical activity and park for some parks by SOPARC method in the case of Konya city (Karatay), Türkiye - Esra Sivri İçöz; Ahmet Tuğrul Polat (Journal of Design for Resilience in Architecture and Planning)
In a rapidly evolving world, technological advancements have brought significant convenience to individuals. However, these developments have increasingly led to a sedentary lifestyle. The need for individuals to regain their natural right to move freely has become more pronounced. Parks, as the largest urban areas facilitating physical activity, play a critical role in addressing this need. This study examines the physical activity levels of park users in three parks in Konya, Türkiye. It also evaluates the park areas and features that enable physical activity. The research identifies the factors that either deter or encourage individuals from utilizing parks and recreational areas for physical activity. In addition, the aim was to calculate how much energy was expended by physical activity in these parks. According to the research findings, the parks have a large number of visitors. The majority of park users are female and the adult age group, while the senior age group prefers parks less. Despite the presence of visitors, inactivity is prevalent in these parks. There are large differences between the number of people in the target areas. While picnic areas are usually densely used, few people who used were observed in sports fields and walking paths. Pearson Chi-Square analysis was used to examine the differences between parks, target areas and periods, park users, and activity levels. The results indicated that among all target areas, picnic areas exhibited the lowest levels of physical activity. Based on these findings, the study offers design recommendations aimed at promoting higher levels of physical activity in parks.